Developing small satellite ground support software for orbit tracking and target acquisition of the HARP cubesat - Sienkiewicz, Noah; Martins, J. Vanderlei; Xu, Xiaoguang; McBride, Brent A.; Remer, Lorraine A. (Frontiers in Remote Sensing, 2024)
Small satellites are efficient at performing Earth science from space due to their limited cost and size. Small satellites (cubesats) achieve much with limited power production/storage, heat dissipation, data storage, and ground contact points/bandwidth. As such it is beneficial to offload as much as possible to ground support systems. Consider the HyperAngular Rainbow Polarimeter (HARP) Cubesat. Its goals were to serve as a technical demonstration prior to the development of HARP2 aboard the NASA Plankton Aerosol Cloud and ocean Ecosystem (PACE) mission and to serve as an Earth viewing remote sensing platform which measured the characteristics of clouds and aerosols. HARP cubesat was limited to taking 5-minute capture sequences once every 24 h. It took approximately 10 such captures before it needed to perform data downlink and have its memory cleared for continued use. A ground station at NASA Wallops supported HARP with approximately three points of contact each day. To maximize the value of each capture, ground support software was developed leveraging public data to inform the schedule of each capture. In this paper, we review the algorithms and data sources that allowed us to: 1; predict the HARP orbital track a week in advance, 2; predict also the location of other remote sensing satellites and ground stations relative to HARP, 3; predict the ground view geometry of the instrument along its orbital track, 4; compare global climatological data products of clouds and aerosols along the predicted orbital tracks, and 5; identify and integrate important ground target locations based on remote sensing literature and ongoing natural phenomena. This HARP Orbital Prediction System (HOPS) made HARP into a successful technical demonstration which also offered significant science value. The HOPS system presents a valuable methodology for small satellites to operate efficiently despite their limited capabilities. HOPS is also a useful testbed for studying the sensitivity of scene geometry. Using HOPS, we show that for a wide field-of-view (FOV) instrument, like HARP, latitude/longitude geolocation varies by approximately 0.1∘ at a height of 8–10 km. Scattering angles vary less than 0.01∘ at similar heights, with the worst performance near direct backscatter 180∘.